ARXETIPIK OBRAZLARNING BADIY VA PSIXOLOGIK TALQINI VA SYUJETLAR TIZIMINING ESTETIK TRANSFORMATSIYASI (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article explores the functional role of archetypal images within the structure of literary texts, the mechanisms of their psychological interpretation, and the aesthetic transformation of plot systems in contemporary literature. Based on Jung’s psychological model and the mythopoetic approach, the study reveals the influence of archetypes on the hero’s psyche, conflict dynamics, and the semantic layers of artistic representation. The analysis examines the reinterpretation of archetypes, the intensification of intertextual relations, and the transformation processes that occur within plot structures and narrative dramatization. The findings demonstrate the dialectical relationship between archetypes, psychological motivation, and artistic composition, confirming the crucial role of the mythic paradigm in the renewal of the aesthetic system.